Analysis of vehicle lane-changing behaviour at signalised intersection. (5th October 2020) - Xing, Yan; Zhang, Zhe; Liu, Weidong; Zhan, Qi; Chu, Chaojun
In order to analyse the characteristics of the lane-changing behaviour at the signalised intersection, the desired speed of vehicle and the lane-changing benefits were studied based on the theory of traffic flow. A vehicle lane-changing model is established, and the adjacent vehicle relative speed, the adjacent vehicle relative distance and the space for the vehicle lane changing are considered. The feasibility of the model is discussed in the fifth part of the paper. Finally we analyse the influence of lane changing behaviour through the actual data. The main content of the analysis is the impact of vehicle lane-changing behaviour on traffic capacity, the results show that traffic flow in the current lane and the traffic flow in the target lane are reduced due to vehicle lane changing at the intersection.